Connection ethnomathematics and ethnomodeling in the bocah sukerta traditional ceremony, Indonesia - Sudirman Sudirman; Ebenezer Bonyah; Jenisus O. Dejarlo; Runisah Runisah; Nandang Nandang; Rosyadi Rosyadi; Mochammad Taufan; Anzzal Ibrahim (Intelektual Pustaka Media Utama, 2026)
This research aims to identify and reveal the connection between ethnomathematics and ethnomodeling in Indonesia’s bocah sukerta traditional ceremony. An ethnographic design was used to reveal the research objectives. The participants involved in this research were the ceremony leader and bocah sukerta. Next, the data obtained from interviews and observations were analyzed using the content analysis method. The research results reveal that the ethnomathematics connection is reflected in weighting activities (weighing objects, calculating total weight, making comparisons, and balancing weights) and the shape of the scales (the basic shape represents 2D geometry, and the frame shape represents 3D geometry). This research also concludes that the ethnomodeling connection produces mathematical understanding, especially in arithmetic operations, weight measurements, weight conversions, mathematical equations, basic statistics, Cartesian coordinates, the center point of a square, and determining a pyramid’s distance, length, and area. Furthermore, this research concludes that the relationship between ethnomathematics and ethnomodeling in the bocah sukerta traditional ceremony can be used to construct didactic designs for square material volumes and rectangular pyramids.